2021
DOI: 10.1177/03057356211055216
|View full text |Cite
|
Sign up to set email alerts
|

“I don’t know how musically creative they should be at that age”: A qualitative study of parents’ and teachers’ beliefs about young children’s creative and musical capacities

Abstract: There has been a recent expansion of school curricula and extra-curricular activities emphasizing musical creativity and collaboration. Parents have a crucial role in providing children with access to such experiences; their views on music and the nature of creativity influence the types of musical engagement their children will access. Teachers also have an important role, yet can have difficulties when supporting children in open-ended tasks. A qualitative study investigated parents’ and teachers’ constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Previous research asserted that parental support and involvement produced positive effects ( Huber, 2019 ; Yuan et al, 2021 ). More intuitively, providing a musical environment, supervising activities at home and investing in children’s musical learning and activities influence children’s personality, identity, communication ability, musical competence, and accomplishments ( Creech and Hallam, 2003 , 2011 ; McPherson, 2008 ; MacGlone et al, 2022 ). Due to these benefits, an increasing number of parents in both the United States (U.S.) and China are willing to send their children to music lessons, and diverse types of music learning patterns have appeared, one of which is taking private lessons.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research asserted that parental support and involvement produced positive effects ( Huber, 2019 ; Yuan et al, 2021 ). More intuitively, providing a musical environment, supervising activities at home and investing in children’s musical learning and activities influence children’s personality, identity, communication ability, musical competence, and accomplishments ( Creech and Hallam, 2003 , 2011 ; McPherson, 2008 ; MacGlone et al, 2022 ). Due to these benefits, an increasing number of parents in both the United States (U.S.) and China are willing to send their children to music lessons, and diverse types of music learning patterns have appeared, one of which is taking private lessons.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies works found that music teachers’ views on creativity resist generalization and are highly dependent on their own experiences in composing music, knowledge of different musical styles, working contexts, or past experiences (Odena & Welch, 2007, 2016). The majority of participants in these studies are located in the Anglosphere world (e.g., MacGlone et al, 2022; Vitale, 2017), with a few exceptions (Schiavio et al, 2023; Sungurtekin, 2021). Likewise, they are typically primary or secondary music teachers, although there are exceptions, such as the study presented in the fourth chapter of Odena (2018), which focuses on developing creativity among conservatoire students.…”
Section: Frameworkmentioning
confidence: 99%